2022
DOI: 10.1111/imj.15732
|View full text |Cite
|
Sign up to set email alerts
|

Prior oral proton‐pump inhibitor use is associated with reduced severity of aspirin‐related upper gastrointestinal bleeding in older people

Abstract: Low-dose aspirin is commonly used for primary or secondary prophylaxis against cardiovascular disease in older people. However, the potential risk of upper gastrointestinal (UGI) ulceration and bleeding associated with low-dose aspirin use is often not appreciated by prescribers and older consumers. Among 133 serial patients with UGI bleeding, aspirin-users aged ≥70 years had a ninefold increased likelihood of overt UGI bleeding compared with non-users, reducing by 90% in regular proton-pump inhibitor users (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Although the amount of purchased low-dose aspirin is difficult to quantify from non-PBS sources, there were 760 717 PBS and Repatriation PBS prescriptions for low-dose aspirin in 2019. 18 It is assumed that the bulk of such prescribed aspirin is for older people, who are more likely to have established atherosclerotic cardiovascular disease (ASCVD) and be at high risk for gastroduodenal ulceration and bleeding. In this journal, three recent independent studies from three states in Australia reported that most non-variceal UGIB episodes in those aged ≥70 years are attributable to low-dose aspirin use.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Although the amount of purchased low-dose aspirin is difficult to quantify from non-PBS sources, there were 760 717 PBS and Repatriation PBS prescriptions for low-dose aspirin in 2019. 18 It is assumed that the bulk of such prescribed aspirin is for older people, who are more likely to have established atherosclerotic cardiovascular disease (ASCVD) and be at high risk for gastroduodenal ulceration and bleeding. In this journal, three recent independent studies from three states in Australia reported that most non-variceal UGIB episodes in those aged ≥70 years are attributable to low-dose aspirin use.…”
mentioning
confidence: 99%
“…In this journal, three recent independent studies from three states in Australia reported that most non-variceal UGIB episodes in those aged ≥70 years are attributable to low-dose aspirin use. [18][19][20] First, among people aged ≥70 years admitted with UGIB to a Western Australian tertiary hospital, those taking regular low-dose aspirin had a nine-fold increased risk of presentation with overt UGIB characterised by haematemesis and/or melaena compared with those not taking aspirin. 18 Three-quarters of older people with UGIB had been taking aspirin.…”
mentioning
confidence: 99%
See 3 more Smart Citations